El Derecho a la seguridad jurídica en las ordenanzas municipales para gestionar los servicios de prevención, protección, socorro y extinción de incendios: GAD Centinela del Cóndor, el Pangui y Saraguro. - House Vivanco, Augusta Vanessa (2019)
The new decentralization model embodied in the 2008 Constitution established that the trans-fer of exclusive competences exclusive rights of the Decentralized Autonomous Governments will be mandatory and definitive. The assumption of the competence of prevention, protec-tion, relief and firefighting services generated with the decentralization process carried out since 2015 was conflicting. The discussion focused on the possible violation of the right to legal security in the assumption of the mentioned competence by the municipalities under study, having ignored the preexisting legal norms that regulated the operation of the fire bri-gade; the fact that these —in accordance with the decentralization process— should be considered as entities attached to municipal GADS. In this framework, the object of this investi-gation is limited to the legal analysis of the process of assumption of competence embodied in the ordinances of the Municipalities of Centinela del Cóndor, El Pangui and Saraguro, in order to determine a possible violation of the right to legal security expressly recognized in the Constitution.